Global Value Chain Governance and Relation between Local Actors in the Burundian Tea Sector - Bitama, Pierre Claver; Lebailly, Philippe; Ndimanya, Patrice; Burny, Philippe (International Review of Management and Marketing, 2019)
In the context of globalization, the success of a firm to sell its products on international and regional markets depends on the type of governance exercised in a given sector. This article mobilizes a theoretical framework of global value chain governance to analyze the type of governance exercised in the tea sector in Burundi. A qualitative analysis of data from a survey of 120 small tea farmers in the Ijenda and Teza areas reveals that control and coordination in the sector is ensured by captive governance. In addition, a stagnation of the price of the green leaf tea over a decade generates a lack of interest in the tea farming out on small farming areas. Only 25% of small tea farmers in Ijenda and 36% in Teza want an extension. Keywords: captive governance, market governance, global value chain, Tea. JEL Classifications: O13, O21, P32, P42 DOI: https://doi.org/10.32479/irmm.8857